Family as a subject of protection in the state family policy = Famille en tant que sujet protégé dans la politique familiale de l’État = La famiglia come oggetto di tutela nella politica familiare statale - Świto, Lucjan (Philosophy & canon law, 2015)
This article analyzes the subject of the state family policy and whether it really serves the protection of the family on the example of Poland. The research carried out leads to the conclusion that the existing state of affairs results in a “blurring” of the traditional culturally and historically conditioned concept of the family, implic-itly introducing its “mental redefinition.” Behind the facade of support for the family, various forms of common coexistence are protected with increasing bold-ness, which also includes―pursuant to the LGBT gender perspective― same-sex couples. The current family policy is not a policy that perceives the family in a comprehensive perspective and is used for the full protection of all family life. The family, although it is a social value with established constitutional position, is not a subject of state protection and support that would be relevant for this position. The existing legal norms rather protect the interests of individual persons belong-ing to the family than the family as a whole. At the same time, the range of per-sons making up a family―according to a trend to extend the definition of a fami-ly―is increasingly widening.